PERSEPSI ORANG TUA TENTANG PORNOGRAFI DAN PENGARUHNYA TERHADAP CARA MENDIDIK ANAK DI DUSUN IV DESA BANGUN SARI BARU KECAMATAN TANJUNG MORAWA - Khairuddin YM; Ahmad Fuadi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2018)
Rapid technology and information advancements significantly improve human lives. People's lives have been made easier by technical advances such as the internet, smartphones, TV, and electricity. This is alarming because it can harm poverty patterns and children's conduct, determining the nation's destiny. Experts convene to devise a "strategy" before making pornographic impressions. The show features neuroscientists, psychologists, and technological experts. So the target market is pre-baliq guys. Boys under the age of 9 who have not reached puberty exhibit a significant interest in pornographic shows. Their parents forbade them from watching the show because they were young.Careless parents let kids steal to view filthy shows. The show will be kept in the limbic system for a long time. Children often have orgasms while watching. They felt guilty at the moment. But, because it's fun, they'll do it again. So parents must be more concerned for their kids. However busy you are, always focus on your child. Eliminate child-parent apathy. It's possible to pay attention to your youngster when busy. Also, the government must strictly enforce restrictions. Protect the kids! The rapid influence of globalization, both in terms of technology and information, is one of the barriers. The propagation of pornography is still not adequately supervised. And solutions to it. Encouraging parents, teachers, and communities to enforce anti-pornography and anti-pornography laws.